CODESRIA Bulletin, Nos 2 & 3, 2021 - Special Issue: Pan Africanism and the Emancipatory Project for Global Africa - Journal System (CODESRIA Bulletin, 2021)
In this issue Editorial Godwin R. Murunga & Ibrahim O. Ogachi........................................................................................3 Éditorial Godwin R. Murunga & Ibrahim O. Ogachi........................................................................................5 1. Introduction: Pan Africanism and the Reparative Framework for Global Africa, _ Horace G. Campbell ............................................................7 2. A Pan-Africanist Approach to Migration, Patricia Daley ...............................................................................17 3. Franc CFA: la farce de mauvais goût de Macron et Ouattara, Fanny Pigeaud & Ndongo Samba Sylla........................................................................23 4. Africa-United States Relations under the Biden Administration: Room for a Pan African Agenda? Cheryl Hendricks.....................................................27 5. Kwame Nkrumah and the Quest for Independence, Adom Getachew....................................................33 6. The Prophecy of Self-Emancipation: Walter Rodney and the Scholarship and Praxis of Defiance in the African World, Michael O. West........................................................... 39 7. Reparations, Knowledge and the Decolonial University, Carole Boyce Davies..............................................43 8. Cyberpower and Pan-Africanism, Abdul Alkalimat & Kate Williams ................................................................................49 9. The Danger of ADOS: How Disinformation Campaigns Threaten Reparations and Pan African Movements through Digital Media, Jessica Ann Mitchell Aiwuyor ................................................................................53 Debates / Débats 10. A Response to Lloyd G. Adu Amoah’s ‘Ghana’s Democracy and the 2020 General Election: Signs of a Fading Promise, Nene-Lomotey Kuditchar .......................................................61 11. Samir Amin : Recueil de textes introduit par Demba Moussa Dembele – Note de lecture, Bernard Founou Tchuigoua .........................................................65